Predicting liver metastases growth patterns: Current status and future possibilities. (June 2021) - Oliveira, Rui Caetano; Alexandrino, Henrique; Cipriano, Maria Augusta; Alves, Filipe Caseiro; Tralhão, José Guilherme
Abstract: Colorectal cancer is highly incident worldwide and presents a health burden with elevated mortality rate despite prevention, detection, and treatment, mainly due to metastatic liver disease. Histological growth patterns of colorectal cancer liver metastases have emerged as a reproducible prognostic factor, with biological implications and therapeutic windows. Nonetheless, the histological growth patterns of colorectal cancer liver metastases are only known after pathological examination of a liver resection specimen, thus limiting the possibilities of pre-surgical decision. Predicting the histological growth pattern of colorectal cancer liver metastases would provide valuable information for patient-tailored medicine. In this article, we perform a review of the histological growth patterns and their implications, with a focus on the possibilities for their prediction.